THE ROLE OF POLYSACCHARIDE KRESTIN FROM Coriolus versicolor MUSHROOM ON IMMUNOGLOBULIN ISOTYPE OF MICE WHICH INFECTED BY Mycobacterium tuberculosis - Permanasari, Adita Ayu (Indonesian Journal of Tropical and Infectious Disease, 2011)
This research was aimed to determine the role of polysaccharide krestin (PSK) with different timing on levels and types of mice immunoglobulin (Ig) isotype which infected by Mycobacterium tuberculosis. This research used 30 adult female mice of Mus musculus strain, polysaccharide krestin was isolated from Coriolus versicolor mushroom, and for infection used Mycobacterium tuberculosis H37Rv (ATCC 27294 T) strain. Provision of polysaccharide krestin was done over 7 consecutive days via gavage. Mycobacterium tuberculosis infection was done 2 times with an interval of 1 week via intraperitoneal. Immunoglobulin isotype serums were analyzed using the ELISA test and the results were analyzed descriptively through the color reaction and OD values. The result showed the highest levels of immunoglobulin was found in the provision of PSK before and after Mycobacterium tuberculosis infection with total 6.280 of OD Ig isotype. Immunoglobulin isotype dominant was IgM with lambda light chain. The conclusion of this research was PSK increased mice Ig isotype levels at the time of provision before, after or before and after infection Mycobacterium tuberculosis. Ig isotype which was formed i.e. IgM, IgA, IgG2b, IgG3, IgG2a, IgG1 with kappa and lambda light chain.